Preparation method of ion exchange nanofiber membrane with high ion exchange capacity
By combining ion exchange resin with electrospinning technology, an ion exchange nanofiber membrane with high ion exchange capacity was prepared, which solved the problem of difficult metal ion pollution in semiconductor chip manufacturing, and achieved efficient, low-cost and environmentally friendly metal ion removal effect.
Patent Information
- Application Number
- CN202411968408.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is difficult to effectively remove metal ion pollution during semiconductor chip manufacturing, resulting in a degradation of chip performance. The common removal methods are costly, low in processing efficiency and prone to secondary pollution.
By combining ion exchange resin with electrospinning technology, an ion exchange nanofiber membrane with high ion exchange capacity is prepared. The membrane has the characteristics of continuous and efficient processing, automatic regeneration and no secondary pollution.
It realizes efficient removal of metal ions in the polishing liquid, improves the adsorption and transfer performance of the material, reduces the processing cost, and avoids secondary pollution.
Smart Images

Figure CN119800607A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of semiconductor polishing liquid treatment, and in particular relates to a method for preparing an ion exchange nanofiber membrane with high ion exchange capacity. Background Art
[0002] Semiconductor chips play a vital role in modern technology and economy. They are the core components of modern electronic devices such as computers, smartphones, tablets, etc., used to build miniaturized circuits that enable these devices to perform complex computing and data processing tasks. The development of semiconductor technology has promoted the revolution in information technology, enabling us to have faster, more efficient and more energy-efficient electronic products. It is also the basis of many emerging technologies such as artificial intelligence, the Internet of Things and wearable devices. Whether from the perspective of technological or economic development, the importance of semiconductors is enormous.
[0003] Wafers are the initial materials for semiconductor chip manufacturing. If they are contaminated by metal ions during the wafer manufacturing process, it is very easy to cause the performance of semiconductor chips to decline and affect the life of the chips. At present, in the CMP process of wafer manufacturing, i.e., chemical mechanical polishing, the components of the slurry used generally include silicon dioxide, aluminum oxide, polymers, complexing agents, dispersants, etc. If the equipment used in the process or the processing slurry is not pure enough and contains metal impurities, these impurities will be adsorbed on the surface of the silicon wafer during the processing or penetrate into the body of the silicon wafer under high temperature conditions. The metal adsorbed on the surface of the silicon wafer can be removed by subsequent cleaning processes, while the body metal is difficult to remove in the subsequent processing, which will have a greater impact on the back-end process. Therefore, in order to avoid metal contamination during mechanical polishing, it is particularly important to ensure the purity of the slurry used in the mechanical polishing process.
[0004] Common methods for removing metal ions include salting out, ion exchange resin, electrochemical methods, etc., which are not only costly and inefficient, but also complicated to operate and prone to secondary pollution. The present invention combines ion exchange resin with electrostatic spinning technology. By incorporating ion exchange resin powder into fiber materials during the electrostatic spinning process, we can prepare a filtering nanofiber membrane with ion exchange function. The membrane treatment process is continuous, efficient and low-consumption, the ion exchange filler is automatically regenerated, and there is no secondary pollution. It has great application prospects in the treatment of low-concentration metal ion polishing liquid.
[0005] The present invention grinds and sieves the ion exchange resin, and then adjusts the addition ratio of the resin to achieve the preparation of a nanofiber membrane with high ion exchange capacity. The membrane is combined with PVDF, a membrane material widely used in industry, so that the membrane has excellent weather resistance, thermal stability, chemical stability and excellent mechanical properties. The nanofiber membrane has a diameter of about 700 nanometers, a high specific surface area and porosity, can provide more adsorption sites, improve the adsorption and transfer performance of the material, and can efficiently remove metal ions in the polishing liquid.
[0006] The nanofiber membrane of the present invention has dual advantages. On the one hand, it inherits the ion selective capture and release ability of ion exchange resins, and on the other hand, it has the unique characteristics of nanoscale polymer fine fibers prepared by electrospinning. This innovative combination is expected to expand the application areas of ion exchange resins and provide more efficient and multifunctional solutions for the removal of metal ions in polishing liquids and other fields. Summary of the invention
[0007] In view of the problems existing in the prior art, the present invention proposes a method for preparing an ion exchange nanofiber membrane with high ion exchange capacity, which adopts PVDF with thermal stability, chemical stability and excellent mechanical properties and a strong acidic cation exchange resin, and produces an ion exchange membrane with the ion selective capture and release ability of the ion exchange resin and the unique characteristics of the electrospun nanoscale polymer fine fibers through electrospinning.
[0008] A method for preparing an ion exchange nanofiber membrane with high ion exchange capacity comprises the following steps:
[0009] 1) Weigh a certain amount of polyvinylidene fluoride, dimethylacetamide and strongly acidic cation exchange resin;
[0010] 2) dissolving polyvinylidene fluoride (PVDF) in a polar solvent (dimethylacetamide (DMAc)) and waiting for the PVDF to dissolve to obtain a PVDF spinning solution;
[0011] 3) grinding the strongly acidic cation exchange resin and adding it to the PVDF spinning solution, stirring evenly to obtain a mixed solution;
[0012] 4) Using the mixed solution as a raw material, electrospinning is performed to prepare a heterogeneous PVDF cation exchange membrane, namely, the ion exchange nanofiber membrane with a high ion exchange capacity.
[0013] Furthermore, in step 1), the mass ratio of polyvinylidene fluoride, dimethylacetamide and strong acidic cation exchange resin is 1:(8.65-8.9):(0.1-0.35), and the strong acidic cation exchange resin is specifically 732 cation exchange resin.
[0014] Furthermore, in step 2), during the PVDF dissolution process, the mixture is heated in a water bath at 55-65° C. with stirring for at least 12 hours.
[0015] Furthermore, in step 3), the particle size of the strongly acidic cation exchange resin is ground to less than 50 μm by a grinder.
[0016] Furthermore, in step 3), the stirring is carried out at 55-65° C. for at least 20 h.
[0017] Furthermore, in step 4), the electrospinning process has a temperature of 35-40°C, a humidity of 27-33%, a syringe thrust speed of 0.6-0.8 mL / h, a voltage of 18-20 kV, a needle inner diameter of 0.3-0.7 mm, a collecting roller of 20-60 revolutions / min, and a distance between the needle and the collecting roller of 15-18 cm.
[0018] An ion exchange nanofiber membrane with high ion exchange capacity is obtained by using any of the methods described above.
[0019] Furthermore, the ion exchange capacity of the heterogeneous PVDF cation exchange membrane reaches 1.7 meq / g, and the fixed charge density is 120 meq / g.
[0020] The heterogeneous PVDF cation exchange membrane is used in the treatment of wastewater containing metal ions, wherein the metal ions include alkali metal ions and / or alkaline earth metal ions, and can be particularly used in the treatment of polishing liquid in the semiconductor manufacturing field.
[0021] Furthermore, after the wastewater containing metal ions is subjected to dead-end filtration at a pressure between 0-80 KPa or cross-flow filtration at a solution flow rate between 0-40 L / min, the total amount of alkali metal ions and alkaline earth metal ions in the treated wastewater is less than 300 mg / L.
[0022] Beneficial effects:
[0023] The present invention designs a material system and improves the film-forming method. The PVDF spinning solution is used as a carrier and a binder. The resin powder is bonded to the inside and the surface of the PVDF spinning solution through electrospinning to obtain an ion exchange membrane having the ion selective capture and release capabilities of the ion exchange resin and the unique characteristics of electrospun nanoscale polymer fine fibers. The ion exchange membrane also has the excellent mechanical properties, mechanical properties, and chemical stability of the PVDF membrane, as well as the advantages of being bendable, cuttable, and shape-controllable. The preparation method of the present application is simple and easy to operate.
[0024] Combining electrospinning technology with ion exchange resin, when the strong acid cation exchange resin meets water, the sulfonic acid group (HSO3 2-) will exchange with metal ions in water, that is, a replacement reaction will occur, thereby removing the metal ions dissolved in water. By changing the addition ratio of the resin, ion exchange membranes with different ion exchange capacities can be obtained. When the ion exchange resin content is less than 1%, the alkali metal and alkaline earth metal ion removal efficiency of the ion exchange membrane is low; when the ion exchange resin content is between 1 and 3.5%, as the content increases, the ion exchange capacity increases from 0.03meq / g to 1.7mmeq / g, Na + , K + , Ca 2+ Mg 2+ The metal ion retention rates increased from 9.43%, 46.20%, 89.25%, 63.33% to 13.22%, 58.23%, 94.08%, 83.16% respectively; however, when the resin content was higher than 3.5%, especially higher than 4%, the structure of the membrane was affected due to the increase in resin content, which directly affected the metal removal efficiency. Therefore, through multiple experiments in the early stage, the resin addition ratio was adjusted, and the performance of the ion exchange membrane obtained could meet the requirements of alkali metal (Na + , K + ), alkaline earth metal ions (Ca 2+ Mg 2+ ) can reduce the total content of alkali metal and alkaline earth metal ions in the solution to less than 300 mg / L. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the preparation process of the PVDF nanofiber membrane of Example 1 of the present invention;
[0026] Figure 2 This is the preparation process of the heterogeneous PVDF cation exchange membrane of Example 2 of the present invention;
[0027] Figure 3 The electrospinning device of the embodiment of the present invention;
[0028] Figure 4 The PVDF nanofiber membrane of Example 1 of the present invention;
[0029] Figure 5 A heterogeneous PVDF cation exchange membrane having a cation exchange resin content of 1% according to Example 2 of the present invention;
[0030] Figure 6 A heterogeneous PVDF cation exchange membrane having a cation exchange resin content of 3.5% according to Example 6 of the present invention;
[0031] Figure 7 The 500-fold electron microscope images of the ion exchange membranes of Example 3 and Example 7 of the present invention are compared. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the accompanying drawings and specific examples.
[0033] Example 1
[0034] like Figure 1 , 4 As shown; the preparation method of the resin-free PVDF nanofiber membrane comprises the following steps: taking a certain amount of white powdery polymer high molecular weight material polyvinylidene fluoride (PVDF) and adding it to polar solvent dimethylacetamide (DMAc), stirring at 60°C for more than 12 hours, and waiting for PVDF to be completely dissolved to prepare 10% PVDF spinning solution; using PVDF spinning solution as raw material, using an electrospinning machine with a needle inner diameter of 0.5mm, setting the voltage to 18kV, the solution advancing speed to 0.6ml / h, the distance between the needle and the collecting drum to 15cm, the collecting drum speed to 20 rpm, the spinning temperature to 35°C, and the humidity to 30%, to prepare the electrospun PVDF nanofiber membrane. The obtained electrospun PVDF nanofiber membrane has a high specific surface area and high porosity, which is conducive to material transmission and exchange; the soft and light material, excellent mechanical properties and chemical stability can be adapted to a variety of occasions, but can only filter tiny particles and cannot remove metal ions.
[0035] Example 2
[0036] like Figure 2 As shown; a method for preparing a heterogeneous PVDF cation exchange membrane comprises the following steps: weighing polyvinylidene fluoride, dimethylacetamide and 732 cation exchange resin in a mass ratio of 1:8.95:0.05; adding white powdery polymer macromolecular substance polyvinylidene fluoride (PVDF) into polar solvent dimethylacetamide (DMAc), stirring at 60°C for more than 12 hours to obtain a PVDF spinning solution; adding 732 ion exchange resin powder with a particle size of less than 50 μm into the PVDF spinning solution, stirring at 60°C for 20 hours to mix evenly, and obtaining a final polymer mixed solution; using the mixed solution as a raw material, using an electrospinning machine with a needle inner diameter of 0.5 mm, setting the voltage to 18 kV, the solution advancing speed to 0.6 ml / h, the distance between the needle and the collecting roller to 15 cm, the collecting roller speed to 20 rpm, the spinning temperature to 35°C, and the humidity to 30%, to obtain a heterogeneous PVDF ion exchange nanofiber membrane. The ion exchange membrane fiber diameter is 600-800nm, and the membrane thickness is 70-80μm. The heterogeneous PVDF ion exchange nanofiber membrane has an ion exchange capacity of 0.03meq / g. When the dead-end filtration pressure is 0-80KPa or the cross-flow filtration flow rate is 0-40L / min, it is difficult to effectively remove alkali metal and alkaline earth metal ions.
[0037] Example 3
[0038] like Figure 2 ,5 As shown; a method for preparing a heterogeneous PVDF cation exchange membrane comprises the following steps: weighing polyvinylidene fluoride, dimethylacetamide and 732 cation exchange resin in a mass ratio of 1:8.9:0.1; adding white powdery polymer macromolecular substance polyvinylidene fluoride (PVDF) into polar solvent dimethylacetamide (DMAc), stirring at 60°C for more than 12 hours to obtain a PVDF spinning solution; adding 732 ion exchange resin powder with a particle size of less than 50 μm into the PVDF spinning solution, stirring at 60°C for 20 hours to mix evenly, and obtaining a final polymer mixture solution; using the mixture solution as a raw material, using an electrospinning machine with a needle inner diameter of 0.5 mm, setting the voltage to 18 kV, the solution advancing speed to 0.6 ml / h, the distance between the needle and the collecting roller to 15 cm, the collecting roller speed to 20 rpm, the spinning temperature to 35°C, and the humidity to 30%, to obtain a heterogeneous PVDF ion exchange nanofiber membrane. The diameter of the ion exchange membrane is 600-800nm, the membrane thickness is 70-80μm, and the ion exchange capacity is 0.3meq / g. When the dead-end filtration pressure is 0-80KPa or the cross-flow filtration flow rate is 0-40L / min, K + Retention rate 46.20%, Na + Retention rate 9.43%, Ca 2+ Retention rate 89.25%, Mg 2+ The interception rate is 63.33%. The electron microscope image of the ion exchange membrane at 500 times magnification is as follows: Figure 7 As shown in a, the resin in the ion exchange membrane is evenly dispersed and there is little agglomeration on the surface of the formed membrane.
[0039] Example 4
[0040] like Figure 2As shown; a method for preparing a heterogeneous PVDF cation exchange membrane comprises the following steps: weighing polyvinylidene fluoride, dimethylacetamide and 732 cation exchange resin in a mass ratio of 1:8.8:0.2; adding white powdery polymer macromolecular substance polyvinylidene fluoride (PVDF) into polar solvent dimethylacetamide (DMAc), stirring at 60°C for more than 12 hours to obtain a PVDF spinning solution; adding 732 ion exchange resin powder with a particle size of less than 50 μm into the PVDF spinning solution, stirring at 60°C for 20 hours to mix evenly, and obtaining a final polymer mixture solution; using the mixture solution as a raw material, using an electrospinning machine with a needle inner diameter of 0.5 mm, setting the voltage to 18 kV, the solution advancing speed to 0.6 ml / h, the distance between the needle and the collecting roller to 15 cm, the collecting roller speed to 20 rpm, the spinning temperature to 35°C, and the humidity to 30%, to obtain a heterogeneous PVDF ion exchange nanofiber membrane. The diameter of the ion exchange membrane is 600-800nm, the membrane thickness is 70-80μm, and the ion exchange capacity is 0.62meq / g. When the dead-end filtration pressure is 0-80KPa or the cross-flow filtration flow rate is 0-40L / min, K + Retention rate 48.73%, Na + Retention rate 10.12%, Ca 2+ Retention rate 90.08%, Mg 2+ The interception rate is 64.51%.
[0041] Example 5
[0042] like Figure 2 As shown; a method for preparing a heterogeneous PVDF cation exchange membrane comprises the following steps: weighing polyvinylidene fluoride, dimethylacetamide and 732 cation exchange resin in a mass ratio of 1:8.7:0.3; adding white powdery polymer macromolecular substance polyvinylidene fluoride (PVDF) into polar solvent dimethylacetamide (DMAc), stirring at 60°C for more than 12 hours to obtain a PVDF spinning solution; adding 732 ion exchange resin powder with a particle size of less than 50 μm into the PVDF spinning solution, stirring at 60°C for 20 hours to mix evenly, and obtaining a final polymer mixture solution; using the mixture solution as a raw material, using an electrospinning machine with a needle inner diameter of 0.5 mm, setting the voltage to 18 kV, the solution advancing speed to 0.6 ml / h, the distance between the needle and the collecting roller to 15 cm, the collecting roller speed to 20 rpm, the spinning temperature to 35°C, and the humidity to 30%, to obtain a heterogeneous PVDF ion exchange nanofiber membrane. The ion exchange membrane fiber diameter is 600-800nm, the membrane thickness is 70-80μm, the ion exchange capacity is 1.3meq / g, and the fixed charge density is 120meq / g. When the dead-end filtration pressure is 0-80KPa or the cross-flow filtration flow rate is 0-40L / min, K + Retention rate 53.62%, Na+ Retention rate 11.48%, Ca 2+ Retention rate 91.58%, Mg 2+ The interception rate is 78.17%.
[0043] Example 6
[0044] like Figure 2 , 6 As shown; a method for preparing a heterogeneous PVDF cation exchange membrane comprises the following steps: weighing polyvinylidene fluoride, dimethylacetamide and 732 cation exchange resin in a mass ratio of 1:8.65:0.35; adding white powdery polymer macromolecular substance polyvinylidene fluoride (PVDF) into polar solvent dimethylacetamide (DMAc), stirring at 60°C for more than 12 hours to obtain a PVDF spinning solution; adding 732 ion exchange resin powder with a particle size of less than 50 μm into the PVDF spinning solution, stirring at 60°C for 20 hours to mix evenly, to obtain a final polymer mixture solution; using the mixture solution as a raw material, using an electrospinning machine with a needle inner diameter of 0.5 mm, setting the voltage to 18 kV, the solution advancing speed to 0.6 ml / h, the distance between the needle and the collecting roller to 15 cm, the collecting roller speed to 20 rpm, the spinning temperature to 35°C, and the humidity to 30%, to obtain a heterogeneous PVDF ion exchange nanofiber membrane. The heterogeneous PVDF ion exchange membrane fiber diameter is 600-800nm, the membrane thickness is 70-80μm, the ion exchange capacity is 1.7meq / g, and the fixed charge density is 120meq / g. When the dead-end filtration pressure is 0-80KPa or the cross-flow filtration flow rate is 0-40L / min, the K + Retention rate 58.23%, Na + Retention rate 13.22%, Ca 2+ Retention rate 94.08%, Mg 2+ The interception rate is 83.16%, the total metal ion content is less than 300 mg / L, and the ion selectivity is Ca 2+ >Mg 2+ >K + >Na + .
[0045] Example 7
[0046] like Figure 2 , 7As shown; the preparation method of heterogeneous PVDF cation exchange membrane includes the following steps: weighing polyvinylidene fluoride, dimethylacetamide and 732 cation exchange resin in a mass ratio of 1:8.4:0.6; adding white powdery polymer high molecular weight polyvinylidene fluoride (PVDF) into polar solvent dimethylacetamide (DMAc), stirring at 60°C for more than 12 hours to obtain PVDF spinning solution; adding 732 ion exchange resin powder with a particle size of less than 50μm into the PVDF spinning solution, stirring at 60°C for 20 hours to mix evenly, to obtain the final polymer mixture solution; using the mixture solution as raw material, using an electrospinning machine with a needle inner diameter of 0.5mm, setting the voltage to 18kV, the solution propulsion speed to 0.6ml / h, the distance between the needle and the collection roller to 15cm, the collection roller speed to 20 rpm, the spinning temperature to 35°C, and the humidity to 30%, to obtain a heterogeneous PVDF ion exchange nanofiber membrane. The 500x electron microscope image of the ion exchange membrane is shown in Figure 7 As shown in b, the resin in the ion exchange membrane is difficult to disperse evenly, agglomerates are formed on the membrane surface, some channels on the fiber surface are blocked, and the fiber structure is poor. When the dead-end filtration pressure is 0-80KPa or the cross-flow filtration flow rate is 0-40L / min, the K + Retention rate 35.73%, Na + Retention rate 6.17%, Ca 2+ Retention rate 77.52%, Mg 2+ The interception rate is 52.48%.
[0047] The above specific embodiments further elaborate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and should not be regarded as limiting the present invention. Within the spirit and principle of the present invention, any modification, equivalent substitution, improvement, etc. of the embodiments should be included in the protection scope of the present invention.
Claims
1. A method for preparing an ion exchange nanofiber membrane with high ion exchange capacity, characterized in that: The steps include: 1) Weigh a certain amount of polyvinylidene fluoride, dimethylacetamide and strongly acidic cation exchange resin; 2) dissolving polyvinylidene fluoride (PVDF) in a polar solvent (dimethylacetamide (DMAc)) and waiting for the PVDF to dissolve to obtain a PVDF spinning solution; 3) grinding the strongly acidic cation exchange resin and adding it to the PVDF spinning solution, stirring evenly to obtain a mixed solution; 4) Using the mixed solution as a raw material, electrospinning is performed to prepare a heterogeneous PVDF cation exchange membrane.
2. The method for preparing an ion exchange nanofiber membrane with high ion exchange capacity according to claim 1, characterized in that: In step 1), the mass ratio of polyvinylidene fluoride, dimethylacetamide and strong acidic cation exchange resin is 1: (8.65-8.9): (0.1-0.35), and the strong acidic cation exchange resin is specifically 732 cation exchange resin.
3. The method for preparing an ion exchange nanofiber membrane with high ion exchange capacity according to claim 1, characterized in that: In step 2), during the PVDF dissolution process, the mixture is heated in a water bath at 55-65° C. with stirring for at least 12 hours.
4. The method for preparing an ion exchange nanofiber membrane with high ion exchange capacity according to claim 1, characterized in that: In step 3), the particle size of the strongly acidic cation exchange resin is ground to less than 50 μm by a grinder.
5. The method for preparing an ion exchange nanofiber membrane with high ion exchange capacity according to claim 1, characterized in that: In step 3), the stirring is carried out at 55-65° C. for at least 20 h.
6. The method for preparing an ion exchange nanofiber membrane with high ion exchange capacity according to claim 1, characterized in that: In step 4), the electrospinning process has a temperature of 35-40°C, a humidity of 27-33%, a propulsion speed of 0.6-0.8 mL / h, a voltage of 18-20 kV, a needle inner diameter of 0.3-0.7 mm, a collecting roller of 20-60 revolutions / min, and a distance between the needle and the collecting roller of 15-18 cm.
7. An ion exchange nanofiber membrane with high ion exchange capacity, characterized in that: The method is obtained by any one of claims 1 to 6.
8. The ion exchange nanofiber membrane with high ion exchange capacity according to claim 7, characterized in that: The heterogeneous PVDF cation exchange membrane has an ion exchange capacity of 1.7 meq / g and a fixed charge density of 120 meq / g.
9. Use of the ion exchange nanofiber membrane according to claim 7 or 8 in the treatment of wastewater containing metal ions, characterized in that: The metal ions include alkali metal ions and / or alkaline earth metal ions.
10. Use of the ion exchange nanofiber membrane according to claim 9 in the treatment of wastewater containing metal ions, characterized in that: After the wastewater containing metal ions is subjected to dead-end filtration at a pressure between 0-80 KPa or cross-flow filtration at a solution flow rate between 0-40 L / min, the total amount of alkali metal ions and alkaline earth metal ions in the treated wastewater is less than 300 mg / L.
Citation Information
Patent Citations
Polymer material for selective adsorption of heavy metal ions based on sulphonic acid resin and preparation method thereof
CN101757893A
Membrane adsorbent for removing heavy metal ions from drinking water effectively and preparation method thereof
CN101961648A
Preparation method of polyvinylidene fluoride (PVDF) hollow ultrafiltation membrane with cation exchange function
CN103212307A
Method for preparing cation exchange film through high-voltage static spinning
CN105297287A
Hydrophilic polyacrylonitrile nanofiber membrane with ion exchange function and preparation method thereof
CN117071168A
Cited By
Nanofiber membrane with high ion exchange capacity and high ion adsorption rate and preparation method
CN120401123A
Nanofiber membrane material with high particulate matter filtering efficiency and metal ion adsorption function and preparation method
CN120844287A